Are you happy at work? Unraveling the roles of social media usage, individual wellbeing and working environment - A.Manaf, Aini Maznina; Tengku Mohd Azzman, Tengku Siti Aisha; Idid, Syed Arabi (2021)
Employee happiness at workplace has been an increasingly popular topic among researchers and scholars in the past two decades due to the rise concern on its role as one of the contributing factors to the positive outcomes in organizations. Despite many studies conducted on employee happiness, limited studies have been focusing on its relationship with social media usage. During the last two decades, social media has infiltrated every aspect of socio-cultural, economic, and human existence at an unprecedented rate. However, little is known whether the social media usage is an antecedent to their happiness at work. This study delineates the potential effects of social media exposure on individual wellbeing and whether this has a favorable effect on their happiness at work. The study delves into the social media usage among employees of manufacturing companies and their impact on their wellbeing, working environment and happiness. A survey involving 475 employees of manufacturing companies in Malaysia was conducted. Results revealed significant relationships between social media usage with job position and income. In addition, the survey results also found significant relationships between individual wellbeing and working environment with happiness at work. Findings of the study will enrich the literature on happiness and social media in organizations. The implications of these findings will be discussed within the framework of social media usage and workplace happiness.